Runaway Train: A Leaky Radiosensitive SCID with Skin Lesions and Multiple Lymphomas - Børre Fevang; Unn Merete Fagerli; Hanne Sorte; Harald Aarset; Håkon Hov; Marit Langmyr; Thomas Morten Keil; Ellen Bjørge; Pål Aukrust; Asbjørg Stray-Pedersen; Tobias Gedde-Dahl (Case Reports in Immunology)
The nuclease Artemis is essential for the development of T-cell and B-cell receptors and repair of DNA double-strand breaks, and a loss of expression or function will lead to a radiosensitive severe combined immunodeficiency with no functional T-cells or B-cells (T-B-SCID). Hypomorphic mutations in the Artemis gene can lead to a functional, but reduced, T-cell and B-cell repertoire with a more indolent clinical course called “leaky” SCID. Here, we present the case of a young man who had increasingly aggressive lymphoproliferative skin lesions from 2 years of age which developed into multiple EBV+ B-cell lymphomas, where a hypomorphic mutation in the Artemis gene was found in a diagnostic race against time using whole exome sequencing. The patient was given a haploidentical stem cell transplant while in remission for his lymphomas and although the initial course was successful, he succumbed to a serious Pneumocystis jirovecii pneumonia 5 months after the transplant. The case underscores the importance of next-generation sequencing in the diagnosis of patients with suspected severe immunodeficiency.